ICT utilization and the information economy: the case of Malaysia - Jaafar, A.S. (Universiti Utara Malaysia, 2002)
Malaysia is taking steps to transform the economy from being production-based to being knowledge driven (K-economy). In line with this objective, information and communication technologies (ICT) have been identified as the strategic enabling tools that will support the growth of the Malaysian economy as well as enhance the living standard of the population. Hence, in the past decade various initiatives have been taken by the government to promote the use and development of ICT. However, there are many issues and challenges that need to be addressed by the country before a successful transformation to a K-economy can be made. One of the issues is ICT utilization for the development of an information society and economy in the country. The paper assesses the current state of ICT utilization in Malaysia based on secondary data. The result indicates that the level of ICT utilization in the country is still low compared to selected countries and there exist wide disparities among states in Malaysia in terms of accessibility to ICT.